Introducing physician associates to hospital patients: Development and feasibility testing of a patient experience‐based intervention - Francesca Taylor; Jonathan Ogidi; Rakhee Chauhan; Zeena Ladva; Sally Brearley; Vari M. Drennan (Wiley, 2021)
Abstract Background Physician associates (PAs) are one of many new mid‐level health practitioner roles being introduced worldwide. They are a recent innovation in English hospitals. Patient confusion with novel mid‐level practitioner titles and roles is well documented, alongside evidence of a positive association between patients' ability to identify practitioners and patient satisfaction. No prior research developed an intervention to introduce PAs or any other new practitioner role to hospital patients. Objective To develop, with patient and public involvement and engagement (PPIE), an intervention for introducing the PA role to hospital patients, and to test feasibility. Methods Intervention development was underpinned by an experience‐based co‐design approach. Workshop participants generated ideas for introducing PAs, subsequently explored in semi‐structured interviews with hospital patients (n = 13). Interview findings were used by participants in a second workshop to design the intervention. Feasibility of the intervention was assessed in relation to its acceptability and efficacy using semi‐structured interviews with hospital patients (n = 20) and PAs (n = 3). Results The intervention developed was a patient information leaflet. It was considered feasible to use in the hospital setting, helpful to patients in understanding the PA role and acceptable to both patients and PAs. The intervention was also appreciated by patients for providing reassurance of care and support. Conclusions An experience‐based co‐design approach enabled development of an intervention tailored to patients' experiential preferences. Positive evidence of feasibility and utility is encouraging, supporting future larger‐scale testing. Patient and public contribution PPIE representatives were involved in the study design, intervention development and data interpretation.